SGS-LTER long-term monitoring project: spotlight rabbit count on the Central Plains Experimental Range, Nunn, Colorado, USA 1994-2006, ARS study number 98 - Stapp, Paul (Colorado State University. Libraries, 1994)
This data package was produced by researchers working on the Shortgrass Steppe Long Term Ecological Research (SGS-LTER) Project, administered at Colorado State University. Long-term datasets and background information (proposals, reports, photographs, etc.) on the SGS-LTER project are contained in a comprehensive project collection within the Repository (http://hdl.handle.net/10217/100254). The data table and associated metadata document, which is generated in Ecological Metadata Language, may be available through other repositories serving the ecological research community and represent components of the larger SGS-LTER project collection. Rabbits are the most important small-mammal herbivores in shortgrass steppe, and may significantly influence the physiognomy and population dynamics of herbaceous plants and woody shrubs. Rabbits also are the most important prey of mammalian carnivores such as coyotes and large raptors such as golden eagles and great horned owls. Two hares (Lepus californicus, L. townsendii) and one cottontail rabbit (Sylvilagus audubonii) occur in shortgrass steppe. In 1994, we initiated long-term studies to track changes in relative abundance of rabbits on the Central Plains Experimental Range (CPER). On four nights each year (one night each season, usually on new moon nights in January, April, July, October), we drove a 32-km route consisting of pasture two-track and gravel roads on the CPER. This was the same route as that driven for carnivore scat counts. Surveys began at twilight. Observers with two spotlights sat in the back of a 4WD pick-up driven at <15 mph. We recorded the perpendicular distance (in m) to each rabbit using a meter tape or range finder; the direction of the rabbit relative to the road; and noted if individuals were solitary or in clusters. We also recorded any carnivores or other animals seen during spotlight surveys. Beginning in Spring 1998, we recorded the vegetation type (habitat) and topographic position of each rabbit seen, as well as position relative to human features, eg windmills, cattle guards, on the landscape. We used the number of rabbits of each species spotted per km of route as an index of relative abundance. We used line-transect approaches in DISTANCE to estimate population densities from perpendicular distance data.
The Short Grass Steppe site encompasses a large portion of the Colorado Piedmont Section of the western Great Plains. The extent is defined as the boundaries of the Central Plains Experimental Range (CPER). The CPER has a single ownership and landuse (livestock grazing). The PNG is characterized by a mosaic of ownership and land use. Ownership includes federal, state or private and land use consists of livestock grazing or row-crops. There are NGO conservation groups that exert influence over the area, particularly on federal lands.
Natural Resource Ecology Laboratory (NREL)
Shortgrass Steppe-Long Term Ecological Research (SGS-LTER)
Keywords: mammals; populations; rabbits; populations dynamics; community dynamics